Remote sensing and gis for spatial analysis of surface water quality and soil pollution - Kreta, D. L.; Klymenko, V. I.; Anpilova, Y. S. (My University, 2018)
The paper presents cartographic models for assessing the quality of soils and surface waters, scientific justification for improving existing monitoring, making operational management decisions for ecological security problems based on the use of modern means of Geographic Information Systems (GIS), methods of remote sensing of the Earth (remote sensing) from space, including through cartographic generalizations of data.
Засоби дзз та гіс для просторового аналізу якості поверхневих вод та забруднення ґрунтів
Keywords: water quality; soil quality; surface water pollution; soils pollution; environmental monitoring; spatial analysis; geographical information systems; remote sensing of the Earth; якість води; якість грунту; забруднення поверхневих вод; забруднення грунтів; екологічний моніторинг; просторовий аналіз; географічні інформаційні системи; дистанційне зондування Землі; 504.45+556.388